Dandelion plot: a method for the visualization of R-mode exploratory factor analyses - Manukyan, Artur; Cene, Erhan; Sedef, Ahmet; Demir, Ibrahim (SPRINGER HEIDELBERG, 2014)
One of the important aspects of exploratory factor analysis (EFA) is to discover underlying structures in real life problems. Especially, R-mode methods of EFA aim to investigate the relationship between variables. Visualizing an efficient EFA model is as important as obtaining one. A good graph of an EFA should be simple, informative and easy to interpret. A few number of visualization methods exist. Dandelion plot, a novel method of visualization for R-mode EFA, is used in this study, providing a more effective representation of factors. With this method, factor variances and factor loadings can be plotted on a single window. The representation of both positivity and negativity among factor loadings is another strength of the method.
Keywords: EFA; Data visualization; R-mode methods; COMMON FACTOR-ANALYSIS; COMPONENT ANALYSIS; NUMBER; PEOPLE; MATRIX; RULES; SPSS; Mathematics